Analysis Of The Planning And Control Functions On Regional Development In Sarmi Regency Province of Papua - Roida Hutabalian (Faculty of Law, Universitas Pekalongan, 2020)
This study aims to determine and analyze the Development Planning System on the supervision of development implementation and what influences the implementation of development in Sarmi Regency, Province of Papua. This research method uses empirical juridical, as an attempt to approach the problem under study with a real legal nature or in accordance with the reality that lives in society. Empirical legal research is research in the form of empirical studies to find theories regarding the process of occurrence and about the working process of law in society. By examining the nature of the law that actually occurs or applies in the field in relation to the analysis of the application of the regional development planning system as a function of supervision of the Implementation of Regional Development in Sarmi Regency Province of Papua.The results obtained show that the function of planning and supervising regional development in Sarmi Regency is so that regions can monitor, measure performance targets, results, and impacts of development programs in a clear and focused manner based on the vision and mission set by the Sarmi Regency Government. The factors that influence development in Sarmi Regency is that there must be mutual coordination between each SKPD in order to be able to develop a development plan program. In addition, there are also various obstacles in development, namely the low quality of Human Resources at the Regency/City level, weak community participation, the tendency of Regency/City governments to close access to information, as well as the struggle for customary rights with customary land owners.